Впровадження молекулярних маркерів в дослідження генетичного поліморфізму м’якої пшениці в південному біотехнологічному центрі в рослинництві - Чеботар, С.В. (Фактори експериментальної еволюції організмів, 2015)
Introduction of molecular markers for genetic polymorphism investigations of bread wheat in South Plant Biotechnology
Center is discussed. The application of molecular markers for analysis of allelic diversities of microsatellite loci, dwarfing
genes (Rht8, Rht-B1, Rht-D1), genes of photoperiod sensitivity (Ppd-A1, Ppd-B1, Ppd-D1) and vernalization response
(Vrn-A1, Vrn-B1, Vrn-D1), genes of puroindolines (Pina-D1, Pinb-D1), genes that determine low content of amylose in
starch of grains (Wx), the genes of storage proteins (Gli-A1, Gli-B1, Gli-D1 and Glu-A3), genes resistance to leaf rust
and the rye translocations in wheat varieties and breeding materials has been shown. There are recommendations to use
molecular markers for creation homogenic wheat varieties, semi-dwarf varieties with shorter heading and flowering
time, varieties with special technological characteristics – soft/ hard, low amylose content. Microsatellite markers which
showed significant associations with frost resistance and other agronomical traits are recommended for marker assisted
selection (MAS) in Ukrainian wheat breeding programs.
Кеуwords: bread wheat, genetic polymorphism, molecular marker, PCR.